Immunologic and pathologic characterization of a novel swine biomedical research model for eosinophilic esophagitis - Cortes, Lizette M.; Brodsky, David; Chen, Celine; Pridgen, Tiffany; Odle, Jack; Snider, Douglas B.; Cruse, Glenn; Putikova, Arina; Masuda, Mia Y.; Doyle, Alfred D.; Wright, Benjamin L.; Dawson, Harry D.; et al. (Frontiers in Allergy, 2022)
Eosinophilic esophagitis (EoE) is a chronic allergy-mediated condition with an increasing incidence in both children and adults. Despite EoE's strong impact on human health and welfare, there is a large unmet need for treatments with only one recently FDA-approved medication for EoE. The goal of this study was to establish swine as a relevant large animal model for translational biomedical research in EoE with the potential to facilitate development of therapeutics. We recently showed that after intraperitoneal sensitization and oral challenge with the food allergen hen egg white protein (HEWP), swine develop esophageal eosinophilia—a hallmark of human EoE. Herein, we used a similar sensitization and challenge treatment and evaluated immunological and pathological markers associated with human EoE. Our data demonstrate that the incorporated sensitization and challenge treatment induces (i) a systemic T-helper 2 and IgE response, (ii) a local expression of eotaxin-1 and other allergy-related immune markers, (iii) esophageal eosinophilia (>15 eosinophils/0.24 mm2), and (iv) esophageal endoscopic findings including linear furrows and white exudates. Thereby, we demonstrate that our sensitization and oral challenge protocol not only induces the underlying immune markers but also the micro- and macro-pathological hallmarks of human EoE. This swine model for EoE represents a novel relevant large animal model that can drive translational biomedical research to develop urgently needed treatment strategies for EoE.